STRENGTHENING STUDENT LITERACY THROUGH NUBDZATUL BAYAN WITH PROBLEM-BASED LEARNING - Khalid Al-Madani (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Currently, awareness of the importance of literacy among students is very low. Literacy is an ability to read and write. All knowledge can be known and even obtained by literacy. Yellow book literacy in pesantren makes a process of interaction or ability in a person. Various types of reading in pesantren ranging from books, articles, wall magazines to yellow books both in Indonesian and Arabic have been neatly arranged on library shelves, only the skills of students need to be honed in order to be able to use them and make additional Islamic insights. Various efforts made by pesantren to strengthen student literacy which has recently experienced a setback, one of which is the Nubdzatul Bayan method, is a method adopted from PP Mambaul Bata-Bata and applied at PP Nurul Abror Al Robbaniyin since 2010. In the method there are several activities including Demonstration, Memorizing Techniques and others that continue to be emphasized to students. This research method uses a qualitative approach type of case study.